Characteristics of Honey Powder with Maltodextrin And Gum Arabic Addition Using Vacuum Foam-Drying Method (Jurnal Ilmu dan Teknologi Hasil Ternak, 2023)
Honey powder is a solution to overcome the weakness of liquid honey. This study aims to determine the characteristics of the addition of maltodextrin and gum arabic as fillers and their ratio to produce the best honey powder characteristics in terms of water content, water activity (aw), hygroscopicity, reducing sugar content, solubility, and dissolving time. This study consisted of 6 treatment levels, namely Maltodextrin 1 (MD1) with a ratio of honey and filler of 2:1 and solid concentration of honey (% d.b) and filler (g) of 40:20, Maltodextrin 2 (MD2) with a ratio of honey and filler of 1:1 and solid concentration of honey (% d.b) and filler (g) of 40:20. b) and filler (g) 40:40, Maltodextrin 3 (MD3) with a ratio between honey and filler of 1:1 and solid concentration of honey (% d.b) and filler (g) 40:60, followed by Gum Arabic 1 (GA1), Gum Arabic 2 (GA2), and Gum Arabic 3 (GA3) which have the same ratio and concentration as the treatment using maltodextrin. In addition, commercial honey powder data was also included as a control (CHP). This study showed that the best moisture content was in MD3, with a value of 0.591%. Then, MD1 at 0.301% had the best result in water activity. In addition, the use of gum arabic has better hygroscopicity compared to maltodextrin. Meanwhile, the results showed that gum arabic gave high reducing sugar content in honey powder compared to the addition of maltodextrin; the more the addition of gum arabic, the higher the sugar content. The use of maltodextrin as a filler in honey powder provides better solubility compared to gum arabic. In addition, the reported addition of maltodextrin can reduce the dissolving time of food powders.